Development of suppressiveness to Fusarium oxysporum in container media and soil amended with fish emulsion and fish hydrolyzed - Bettiol, W.; Forner, C. [UNESP]; Mattos, L. P.V. (International Society for Horticultural Science (ISHS), 2014)
Fusarium wilt is caused by Fusarium oxysporum f. sp. lactucae and F. oxysporum f. sp. lycopersici, which are soilborne fungal pathogens that cause serious losses in lettuce and tomato, respectively. Commercial formulations of container media in Brazil are conducive to these diseases. The incorporation of organic residues to induce suppressiveness in container media is an alternative of control with a sustainable disposal of rural and urban residues. This study aimed to evaluate the potential of fish hydrolyzed (FH) and fish emulsion (FE) to induce suppressiveness against these pathogens in container media. FH was added to the infested substrate with F. oxysporum f. sp. lycopersici at concentrations of 0-50% of the volume of water required to reach the water retention capacity and the mixtures were incubated for 10 days, followed by planting seedlings of tomato. FH reduced the disease incidence and severity in tomato, as well as increased plant growth. For F. oxysporum f. sp. lactucae, FH and FE inhibited microconidia germination in >88 and >83%, in the concentrations of ≥10 and ≥20%, respectively, in the substrate. We concluded that FE and FH induced suppressiveness in the substrate to these soilborne fungi pathogens.
Keywords: Fusarium wilt; Lettuce; Organic matter; Soil suppressiveness; Tomato